Prediksi Kunjungan Wisatawan Mancanegara Ke Indonesia Menggunakan Jaringan Saraf Tiruan Dengan Algoritma Backpropagation - Opriyani Armaya Putri; P Poningsih; Heru Satria Tambunan (LPPM STIKOM Tunas Bangsa, 2021)
This study aims to see the development of the number of foreign tourist arrivals in the following year. With these predictions, it is expected to be able to assist the government in making policies related to foreign tourists in accordance with their home regions. Sources of data obtained from the Central Statistics Agency. In this study, researchers used the Backpropagation Algorithm. Backpropagation Algorithm is an algorithm that serves to reduce the error rate by adjusting the weight based on the desired output and target. From the test results of foreign tourist visit data obtained in 1-4-1 architecture which shows the target is reduced by the output that SSE 1.03218 which shows that there is an increase in the number of visits as a target. From the data obtained, that the performance calculation of artificial neural networks with Backpropagation Algorithm is 83.3This research contributes to the government and the community to further increase the provision of facilities, infrastructure, infrastructure, transportation and accommodation in order to get a satisfying predicate to improve the quality of the world market.